The experience of the desire to be: bond of resistance for women - Sánchez Leyva, María José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This proposal is inscribed in the framework of analysis and understanding of contemporary processes of subjectivation as ways of imposing an essence on an existence. Since we have been built with the images of others, we women have had to build ourselves with them. Although the outcomes of this construction are very diverse, we are similar in sharing a particular way of bonding: the experience of the desire to be. Being always without doing, we are always being and each woman is the result of one resolution that allows us to live.